2022
DOI: 10.1186/s12889-022-12778-w
|View full text |Cite
|
Sign up to set email alerts
|

“It’s how we get to know each other”: Substance use, connectedness, and sexual activity among men who have sex with men who are living with HIV

Abstract: Background Among MSM, substance use increases risk for acquiring HIV and is associated with sub-optimal engagement in HIV-related care. Most research related to substance use and sexual activity among MSM focuses on identifying and reducing risk of HIV acquisition and transmission rather than pleasure and agency. However, substance use may also facilitate sexual pleasure and build community, which could be particularly meaningful for individuals who cope with intersecting stigmas related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…People living with stigmatized identities (e.g., sexual orientation -men who has sex with men, HIV diagnosis, socioeconomic status) may also use substances during sexual intercourse to build intimacy or strengthen connections that they struggle to find elsewhere. Individuals also used substance to decrease painful emotions, relieve psychological suffering, and maintain emotional stability and control [13]. These findings suggest that a comprehensive, interdisciplinary approach is obligatory to enable the attainment of a healthy approach to sexual life and there is a need for mental health support which should be among the interventions offered to MSM engaging in chemsex.…”
Section: High-risk Sexual Behaviour: Chemsexmentioning
confidence: 99%
“…People living with stigmatized identities (e.g., sexual orientation -men who has sex with men, HIV diagnosis, socioeconomic status) may also use substances during sexual intercourse to build intimacy or strengthen connections that they struggle to find elsewhere. Individuals also used substance to decrease painful emotions, relieve psychological suffering, and maintain emotional stability and control [13]. These findings suggest that a comprehensive, interdisciplinary approach is obligatory to enable the attainment of a healthy approach to sexual life and there is a need for mental health support which should be among the interventions offered to MSM engaging in chemsex.…”
Section: High-risk Sexual Behaviour: Chemsexmentioning
confidence: 99%
“…However, drug use motivations are complex and might vary by population. Following a thematic analysis approach, Stanton et al showed that substance use was considered (1) a way to increase intimacy and have better sexual intercourse; (2) a pathway to improve access to partners and gain entry to a community; and (3) a potential way for empowerment (27). is a stimulant that powerfully activates brain chemicals linked to feelings of reward and pleasure.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulant use (referred to here as usage of methamphetamine, crack-cocaine and/or powder cocaine) among sexual minority men who have sex with men (SMM) is up to 20 times more prevalent than in the general population [ 1 ]. Stimulants, especially methamphetamine (meth), can be used by SMM for increased energy and for sexual pleasure, reducing inhibitions, prolonging sexual encounters and has been associated with HIV-vulnerability through related risk behaviors [ 2 , 3 ]. Miami-Dade, Broward and Palm Beach counties (South Florida) ranked first in US HIV incidence from 2015 to 2019, is consistently in the top five metropolitan statistical areas in the US [ 4 ] and is a priority jurisdiction in the Ending the HIV Epidemic (EHE) plan [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have highlighted the role of stimulants in sexualized drug use for SMM, such as “party and play (PnP)” or “parTy” in North America [ 3 , 7 , 8 ]. Combining stimulant such as meth with amyl nitrites (i.e., poppers) and erectile dysfunction drugs (PnP) can be used to increase libido, social connectedness and enhance sexual experiences[ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation